Triadic partnerships: Evaluation of a group mentorship scheme - Foss, Anna M; Kohler , Sophia; Kulkarni , Sumedh; Sutton , Natalina; Schreiner , Mary-Ann; Centemero, Nicolò Saverio; Mambula , Grace; Lohman , Diederik; Smith , Sarah C; French, Rebecca (International Journal for Students as Partners, 2022)
We synthesised views and experiences of three teams (student mentees, alumni mentors, and staff) in our pilot mentorship scheme within a distance learning MSc, evaluated the scheme, and developed a conceptual model of “triadic partnerships.” Thematic analysis of our qualitative data revealed a strong consensus across all teams. The triadic partnerships were reported to help reduce the feeling of “distance” in distance learning. Through developing triadic partnerships, our mentorship scheme provided added value beyond that offered previously by staff alone: credible and relatable authenticity within supportive mentoring by alumni. Since the scheme’s launch, student engagement has increased, with high levels of reported satisfaction and positive feedback and greater confidence among all teams. Our research connects the framework developed by Healey et al. (2014, 2016) to the literature on mentoring, offering a conceptual model on triadic partnerships. We encourage readers to consider the different relationships within multidimensional student partnerships in their own contexts.